DESCRIPTOR AS A FRAMEWORK FOR DEFINING LANGUAGE SKILL DEVELOPMENT ACROSS PROFICIENCY LEVELS (Global Conference on Multidisciplinary Research and Innovation, 2026)
Due to globalization processes, the demand for qualified specialists who know foreign languages is rapidly increasing in all professional fields. Language and linguistic education have become tools for international professional communication and an important cultural element for successful social development. As a result, the need, demand, and motivation to learn foreign languages, especially English, continue to grow. The relevance of this research lies in the fact that developing pragmatic competence is connected with a person’s readiness and ability to adapt to changes in professional activity. It is considered an integral personality characteristic. To describe the process of developing pragmatic competence in higher education, modeling methods widely used in pedagogy were applied.
Keywords: activity-based, vocabulary acquisition, self-regulated learning, involvement load hypothesis, artificial intelligence, the ability to overcome misunderstandings multimodal input, dual coding theory, cognitive load theory, adaptive learning systems, online dictionaries, corpora, interactive learning platforms.